An empirical investigation of information sharing behavior on social commerce sites. Issue 5 (October 2016) - Liu, Libo; Cheung, Christy M.K.; Lee, Matthew K.O.
Highlights: This study highlights the role of directed social network and examines its impact on information sharing behavior. The model was test by analyzing data collected with both subjective and objective approaches in a longitudinal setting. This study examines customer information sharing behavior in a new social media context – social commerce sites. Abstract: Social commerce sites (SCSs), a new model of social media, provide fertile ground for customers to communicate their opinions and exchange product- or service- related information. Given the significant opportunities related to the use of social media data for customers' insight, we explore the factors driving information sharing behavior on SCSs. In this paper, we propose and empirically test a comprehensive theoretical model for customer information sharing behavior through analysis of online survey data as well as network and behavioral usage data of over four months from 1177 customers in a SCS. The research model was empirically validated with the use of both subjective and objective data in a longitudinal setting. Our results show that customer information sharing is influenced by both individual (i.e., reputation and the enjoyment of helping others) and social capital (i.e., out-degrees' post, in-degrees' feedback, customer expertise and reciprocity) factors. This study contributes to the existing literature by highlighting the role of directed social network in customer information sharing behavior on SCSs. We believe that the results of our study offer important insights to the IS research and practice.